Accompanying your children: Living without parents at different stages of pre-adulthood and individual physical and mental health in adulthood - Jiang, Yao; Xiao, Hanling; Yang, Fan (Frontiers in Public Health, 2023)
Objectives: This study examined how living without parents at different stages of childhood and adolescence affects physical and mental health in adulthood. Methods: The data came from 3,464 survey respondents aged 18 to 36 in the 2018 China Labor-Force Dynamics Survey. Physical health was self-rated. Mental health was measured by the Center for Epidemiological Studies Depression (CES-D) scale. The ordered probit and ordinary least-squares regression analyses were employed to determine the associations between growing up without parents at different stages in pre-adulthood and individual physical and mental health in adulthood. Results: Individuals who did not live with their parents during their minor years were more likely to report worse physical and mental health in adulthood, compared to those who lived with their parents. This difference was heterogeneous among different age stages and genders. Conclusions: Absence of parents in the household has long-term impacts on the physical and mental health of children in adulthood, especially for females. The government should make feasible institutional arrangements to avoid the separation of minor children from their parents.